2006
DOI: 10.1111/j.1462-2920.2006.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to elevated zinc concentrations induced structural changes and zinc tolerance of the nitrifying community in soil

Abstract: A series of long-term Zn-contaminated soils was sampled around a galvanized pylon. The potential nitrification rate (PNR) was unaffected by the soil total Zn concentrations up to 25 mmol Zn kg(-1) whereas spiking the uncontaminated control soil with ZnCl(2) to identical total concentrations completely eliminated nitrification. The larger sensitivity of the PNR to spiked ZnCl(2) than to the Zn added in the field was equally found when relating the PNR to the Zn concentrations in the pore water of these soils, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…Therefore, PNRs could be a sensitive parameter in the soil Hg pollution diagnostics as well, especially in the early diagnostics since there were no dose-response relations found in the treatments over 1 week incubation in this study. Mertens et al (2006) mentioned the same phenomena in the study using Zn as a stressor, stating that the long-term Zn pollution could hardly change the PNRs in the soil.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Therefore, PNRs could be a sensitive parameter in the soil Hg pollution diagnostics as well, especially in the early diagnostics since there were no dose-response relations found in the treatments over 1 week incubation in this study. Mertens et al (2006) mentioned the same phenomena in the study using Zn as a stressor, stating that the long-term Zn pollution could hardly change the PNRs in the soil.…”
Section: Discussionmentioning
confidence: 66%
“…It was also reported that there was no significant difference in the number of 16S rRNA gene fragment of AOB using most probable number method (Mertens et al 2006). Phylogenetic analysis of the bacterial amoA gene sequences indicated that Nitrosospira cluster 3 was the dominant AOB group and the community composition changed with different soil Hg concentrations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been hypothesized that recovery of nitrification following Zn exposure is due to the development of Zn-tolerant AOB populations (Mertens et al, 2006). However, the recent insights into the role of AOA in soil ammonia oxidation (Leininger et al, 2006) place the role of AOB in nitrification restoration in doubt.…”
Section: Introductionmentioning
confidence: 99%
“…Zn tolerance was tested in the unexposed and the Zn-exposed soil samples at T0 to T3 using the spikeon-spike test of Mertens et al (2006). In short, ZnCl 2 was added to duplicate suspensions of soil samples (1:10 soil/CaCl 2 0.01 M ratio) to final concentrations of 0, 0.77, 1.5 and 3.1 mM added Zn.…”
Section: Zn-tolerance Testingmentioning
confidence: 99%